William Diller Matthew's Early Years in New Brunswick and the Giant Trilobite - Miller, Randall (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1994)
Abstract Many stories surrounding paleontological discoveries are just as exciting and mysterious as the fossils themselves. Canadian history includes accounts of dinosaur hunting expeditions in the Alberta bad lands and the often told story of Walcott's discovery of fossils in the Burgess Shale in British Columbia.While some of these tales make it to the public realm, most circulate only within the geological community, surfacing as anecdotes to enrich textbooks and geology courses. New Brunswick's paleontological history has a few such stories although, until recently, much of the ear-ly exploration was not well documented.Included among the province's notable scientists is paleontologist William Diller Matthew (1871-1930) who spent his early years in Saint John and Fredericton and was associated with the discover yof Paradoxides regina, a large trilobite described by his father in 1887 It is thisstory that requires reevaluation based on recent research that uncovered newdetails about the discovery of P. regina.